Phenolic profile and antimicrobial activity of different dietary supplements based on Cochlospermum angolensis Welw - Pereira, Carla (2015)
Three different formulations (infusion, pills and syrup) of Cochlospermum angolensis were characterized by HPLC-DAD-ESI/MS regarding phenolic composition, and evaluated by their in vitro antimicrobial activity against clinical isolates of multiresistant bacteria. Infusion and pills showed the highest variety of phenolic compounds, with eleven molecules identified. Protocatechuic acid was only present in infusions, being the most abundant compound, while (epi)gallocatechin-O-gallate was the main molecule identified in pills and eucaglobulin/globulusin in syrup. Infusion revealed antimicrobial activity against all the studied bacteria with the exception of Proteus mirabilis whereas the pills revealed activity in Escherichia coli spectrum extended producer of β-lactamases and methicillin-resistant Staphylococcus aureus. In the syrup there was no antimicrobial activity detected, which is in agreement with its low concentrations of phenolic compounds. None of the formulations inhibited P. mirabilis. Considering the obtained results, C. angolensis infusion can be considered a good source of phenolic compounds as well as a good antimicrobial agent.